Methods of radiation and environmental studies of build-up areas and their analysis; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Ryzhakova (Rizhakova) N. K. Nadezhda Kirillovna; Shilova K. O. Ksenia Olegovna; Udalov А. А.; Demyanenko N. V. Natalia Vladimirovna (Radiation physics and chemistry of condensed matter, 2017)
Title screen